First report of Lactococcus garvieae from bovine mastitis in Türkiye characterizing some adhesion-related virulence genes and antimicrobial resistance profiles - Nuhay, C.; Çelik, A.E.; Yalcin, S. (Polish Journal of Veterinary Sciences, 2026)
This research explored the distribution of adhesion-associated virulence determinants and analyzed the antimicrobial susceptibility characteristics of Lactococcus garvieae isolates recovered from bovine mastitis milk samples. Samples were obtained from dairy cows diagnosed with mastitis between 2020 and 2025 and were subsequently sent to the Microbiology Laboratory at the Bornova Veterinary Control Institute (Türkiye) for bacteriological analysis. Polymerase chain reaction (PCR) was performed to detect the presence of adhesion-associated virulence genes, including pavA, psaA, LP1-P4, AC1, AC2 and AF in the L. garvieae strains. Antibiotic susceptibility of the isolates was examined using the disk diffusion method, and multidrug-resistant strains that were resistant to at least three antimicrobial classes were identified. Molecular analyses revealed that pavA, psaA, LP3, AC1 and AC2 genes were present in all isolates (100%). The AF, LP1, and LP4 genes were each detected in two isolates (20%), while LP2 was identified in only one isolate (10%). According to antibiotic susceptibility results, all isolates were susceptible to florfenicol and ampicillin (100%). The highest resistance rate was observed against ciprofloxacin (90%), followed by oxytetracycline and sulfamethoxazole/trimethoprim (80%), penicillin and enrofloxacin (70%), spectinomycin (60%), and erythromycin (40%). Multidrug resistance was detected in nine of the ten isolates (90%), whereas one isolate was resistant only to β-lactams and fluoroquinolones. This study provides the first data on the virulence characteristics of L. garvieae strains isolated from bovine mastitis milk samples in Türkiye. The findings demonstrate that these isolates harbor adhesion-related virulence genes and exhibit a high prevalence of multidrug resistance. These results highlight the pathogenic potential of L. garvieae in bovine mastitis; however, further studies are needed to better elucidate its pathogenic mechanisms, genetic diversity, and resistance traits.